The SCIDOTS Project: evidence of benefits of an integrated tobacco cessation intervention in tuberculosis care on treatment outcomes - Awaisu, Ahmed; Nik Mohamed, Mohamad Haniki; Mohamad Noordin, Noorliza; Abd Aziz, Noorizan; Syed Sulaiman, Syed Azhar; Muttalif, Abdul Razak; Ahmad Mahayiddin, Aziah (BioMed Central, 2011)
Background: There is substantial evidence to support the association between tuberculosis (TB) and tobacco smoking and that the smoking-related immunological abnormalities in TB are reversible within six weeks of cessation. Therefore, connecting TB and tobacco cessation interventions may produce significant benefits and positively impact TB treatment outcomes. However, no study has extensively documented the evidence of benefits of such integration. SCIDOTS Project is a study from the context of a developing nation aimed to determine this. Methods: An integrated TB-tobacco intervention was provided by trained TB directly observed therapy shortcourse (DOTS) providers at five chest clinics in Malaysia. The study was a prospective non-randomized controlled intervention using quasi-experimental design. Using Transtheoretical Model approach, 120 eligible participants who were current smokers at the time of TB diagnosis were assigned to either of two treatment groups: conventional TB DOTS plus smoking cessation intervention (integrated intervention or SCIDOTS group) or conventional TB DOTS alone (comparison or DOTS group). At baseline, newly diagnosed TB patients considering quitting smoking within the next 30 days were placed in the integrated intervention group, while those who were contemplating quitting were assigned to the comparison group. Eleven sessions of individualized cognitive behavioral therapy with or without nicotine replacement therapy were provided to each participant in the integrated intervention group. The impacts of the novel approach on biochemically validated smoking cessation and TB treatment outcomes were measured periodically as appropriate. Results: A linear effect on both 7-day point prevalence abstinence and continuous abstinence was observed over time in the intervention group. At the end of 6 months, patients who received the integrated intervention had significantly higher rate of success in quitting smoking when compared with those who received the conventional TB treatment alone (77.5% vs. 8.7%; p < 0.001). Furthermore, at the end of TB treatment (6 months or later), there were significantly higher rates of treatment default (15.2% vs. 2.5%; p = 0.019) and treatment failure (6.5% vs. 0%; p = 0.019) in the DOTS group than in the SCIDOTS group. Conclusion: This study provides evidence that connecting TB-tobacco treatment strategy is significant among TB patients who are smokers. The findings suggest that the integrated approach may be beneficial and confer advantages on short-term outcomes and possibly on future lung health of TB patients who quit smoking. This study may have important implications on health policy and clinical practice related to TB management among tobacco users.